2017
DOI: 10.1038/bcj.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

CXorf48 is a potential therapeutic target for achieving treatment-free remission in CML patients

Abstract: Although the introduction of tyrosine kinase inhibitors (TKIs) has improved overall survival of patients with chronic myeloid leukemia (CML), about half of the patients eventually relapse after cessation of TKIs. In contrast, the remainder of the patients maintain molecular remission without TKIs, indicating that the patients’ immune system could control proliferation of TKI-resistant leukemic stem cells (LSCs). However, the precise mechanism of immunity against CML-LSCs is not fully understood. We have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…CXorf48 is a CTA that is expressed in chronic myelogenous leukaemia cells and not in normal blood cells [11]. This antigen is also detected in some of solid cancers including head and neck carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CXorf48 is a CTA that is expressed in chronic myelogenous leukaemia cells and not in normal blood cells [11]. This antigen is also detected in some of solid cancers including head and neck carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…CTAs located inside the cells are processed by the proteasome, modified by the endoplasmic reticulum and Golgi apparatus, moved to cell surface, and finally presented by the HLA molecule. We previously identified an epitope, CXorf48 [49][50][51][52][53][54][55][56][57] , which binds to HLA-A*24;02, the most popular HLA class I haplotype in the Japanese population [11]. PRAME, another CTA located in the 22 nd chromosome [24], was also strongly expressed in all myeloma cell lines, which is consistent with reports that gene expression levels are lower in X chromosomal genes compared to autosomal genes [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that CT55 is a potential novel immune target for achieving treatment-free remission in chronic myeloid leukemia patients 27 , which prompted us to investigate whether CT55 affects immune and inflammatory responses during the process of CAC. Analysis of the mechanisms by which CT55 mediates a significant effect on CAC revealed that TNF-α-induced NF-κB signaling is the major downstream target.…”
Section: Discussionmentioning
confidence: 99%